Rancangan Aplikasi Penitipan Hewan Berorientasi Objek pada Juanda Petshop and Clinic Depok - Ika Mei Lina (Universitas Indraprasta PGRI Jakarta, 2018)
Animal care service offered by petshops is one of the best solutions for most Indonesians who cannot bring along their pets during their long-distance traveling. It is seen as a good business opportunity by the owner of Juanda Petshop and Clinic Depok. However, in doing its business process, it usually uses a manual recording which sometimes causes losses both in terms of material and customer trust. The purpose of this research is to deal with the problem by designing a well-integrated and organized pet management system by utilizing the rapidly evolving information technology. The method used in this study is a qualitative approach by which the data on the related problems are collected and studied. The result of the research shows that the design of animal care service application in Juanda Petshop and Clinic Depok can be a good solution to improve the quality of service.